An Interpretative Phenomenological Analysis exploring Educational Psychologists’ experiences of the Channel Panel and working with young people who have been identified as being at risk of “radicalisation” - Hywel-Edwards, Lauren (2024)
Over recent years, there has been an increase in young people becoming identified as being at risk of “radicalisation” (Home Office, 2023a). There is limited research exploring the psychological factors underpinning the development of adopting “extremist” views. The systematic review highlighted several psychological aspects which could contribute to young people developing “radicalisation” (Brown et al., 2021; Gaudette et al., 2022; Ellefsen & Sandberg, 2022; Pilkington & Hussain, 2022; Ghosh et al., 2023). Current literature recognises the importance of psychology and the potential role Educational Psychologists (EPs) have to provide support in this area (Sewell & Hulusi, 2016; Lee & Woods, 2017; D’Lima, 2019). Since the introduction of the Prevent Agenda (2011) and subsequent development of the Channel Programme (2012), there has been an increased number of referrals made by professionals to support young people who are at risk of “radicalisation” (Home Office, 2023a). The Channel Panel consists of a range of professionals that aim to provide support to young people who have been referred due to concerns regarding “radicalisation”. Currently, there is no requirement for EPs to be present at panel meetings (Home Office, 2023a; Cook & Schneider, 2024). However, in some authorities, EPs have regularly attended panel meetings and supported with discussions of cases bought to panel involving young people (Augestad Knudsen, 2017). At present, there is no research into EPs’ experiences of the Channel Panel. Therefore, this study aimed to explore EP experiences of the Channel Panel as well as considering how they could provide support for young people identified as being at risk of “radicalisation”. The research aimed to gain an understanding of the lived experiences through an Interpretative Phenomenological Analysis. Five UK based EPs were recruited and data was gathered using semi-structured interviews. Four interconnected Group Experiential Themes were interpreted as being key to EPs’ lived experiences: the contribution of psychology is essential, encouraging others to consider a different perspective, the importance of developing professional relationships and the personal impact of EP involvement. These interpretations are explored in relation to pertinent literature and research. A methodological review follows where limitations of the study are considered. The implications for the Channel Panel, EP practice and the local authority which indicate the importance of EP contribution to Channel Panel discussions, particularly when cases involve young people with additional needs, are presented.